Determination of Household Food Consumption Patterns in East Baturaja District OKU Regency - Veranita, L; Munajat, Munajat; Sari, Y; Sari, Fifian Permata (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
The income level will influence household spending patterns. In conditions of limited income, low-income or poor households will prioritise allocating their income to buying food. This income will be used to spend on food for survival so it will affect the quantity and quality of household food consumption. Good quality food consumption indicates that nutritional adequacy levels are met. This research analyses the factors influencing household food consumption patterns in East Baturaja District, OKU Regency. This research used a survey method and was carried out in three sub-districts in East Baturaja District, OKU Regency, namely Kemala Raja, Sekar Jaya and Tanjung Baru Villages. The method for determining respondents is random sampling using the Parell et all (1973) formula with the statement if the variance of the total population is unknown, so the best way to determine the sample is to use a percentage of the entire population, namely 2%, 5%, 10%, 20% or 50% of the population. The population is 2126 families, obtained by 2%, namely 42.52 and determined to be 43 families. This research used multiple linear regression models to determine the factors influencing food consumption patterns using multiple linear analyses. Based on the research results, it can be concluded that the factors that influence household food consumption patterns in East Baturaja District, OKU Regency, are income (X1), number of family members (X2), age (X3), and education level (X4). The variable that has the most influence on household food consumption patterns in East Baturaja District, OKU Regency, is the income level variable (X1). Simultaneously or together, the income variable (X1), number of family members (X2), age (X3), and education level (X4) has a significant influence. R2 showed this with a value of 97.9%.